2015
DOI: 10.1039/c5sc02269j
|View full text |Cite
|
Sign up to set email alerts
|

The ligand unwrapping/rewrapping pathway that exchanges metals in S-acetylated, hexacoordinate N2S2O2complexes

Abstract: The effect of S-acetylation in MN2S2 complexes on metal exchange reactivity was examined in a series of MN2S2O2 complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…In MeOH or H 2 O solution, [ Ni-I ] 0 is distinctly blue, in agreement with absorptions of 378 and 600 nm. Note that the bis-acetylated NiN 2 S 2 complex, the octahedral NiN 2 S′ 2 O 2 whose structure is shown in Figure b, is cobalt blue in the solid state and also in aqueous solution . The solid-state UV–vis spectra of NiN 2 S′ 2 O 2 and [ Ni-I ] 4 0 complex are given in Figure S17 and are qualitatively similar, as expected due to the similar first coordination spheres around the Ni­(II).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…In MeOH or H 2 O solution, [ Ni-I ] 0 is distinctly blue, in agreement with absorptions of 378 and 600 nm. Note that the bis-acetylated NiN 2 S 2 complex, the octahedral NiN 2 S′ 2 O 2 whose structure is shown in Figure b, is cobalt blue in the solid state and also in aqueous solution . The solid-state UV–vis spectra of NiN 2 S′ 2 O 2 and [ Ni-I ] 4 0 complex are given in Figure S17 and are qualitatively similar, as expected due to the similar first coordination spheres around the Ni­(II).…”
Section: Resultssupporting
confidence: 56%
“…Similar MN 2 S′ 2 O 2 (S′ = thioether; O = carboxylato) octahedral complexes with M = Fe 2+ , Co 2+ , Ni 2+ , Zn 2+ demonstrated that a path was opened for metal ion exchange in the hexadentate ligand resulting from such acetylations. While such a metal exchange could not be directly achieved in the parent [MN 2 S 2 ] complexes, where S-bridged aggregates prevailed in the products, the acetylated complexes demonstrated the hierarchy expected by the Irving–Williams series Fe 2+ < Co 2+ < Ni 2+ < Cu 2+ > Zn 2+ . , Kinetic parameters were consistent with a ligand-unwrapping process that involved carboxylate oxygens as bridges between coordination spheres prior to metal swapping . In support of this hypothesis, the acetylated CuN 2 S′ 2 O 2 complex was isolated with one detached thioether, extending its carboxylate arm to bind a second Cu 2+ (Figure c), forming a dimeric structure .…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…No X-ray structure of other cobalt complexes with a coordination sphere composed of two phenolate, two thioether and two pyridine donors are available for comparison. However, the structural parameters of complex 2•py could be compared to other cobalt(II) complexes presenting an O2S2N2 coordination sphere, with O = phenolate, alkoxide or carboxylate, S = thioether and N = pyridyl or neutral amine donors[58][59][60]. The ranges of the Co-O [1.952(3)-2.033(2) Å], Co-N [2.134(3)-2.198(3) Å] and Co-S [2.478(2)-2.657(1) Å] bond lengths in these compounds encompass those observed for 2•py (see above).…”
mentioning
confidence: 99%